ANALISIS SENTIMEN TOPIK VIRAL DESA PENARI PADA MEDIA SOSIAL TWITTER DENGAN METODE LEXICON BASED - Rifiana Arief; Karel Imanuel (Jurnal Ilmiah Matrik, 2019)
Abstract : The horror story of Dancer Village in Indonesia is a viral topic that has become a talk of citizens on Twitter social media. Various responses and public opinions emerged related to the truth of the story of supernatural experiences of students during a Real Work Lecture in an East Java region of Indonesia. This study conducted a sentiment analysis of community comments on Twitter social media on the viral topic using the Lexicon Based method. Sentiment classification is divided into 3 classes namely positive, negative and neutral. The research phase consists of data collection, pre-processing, processing (sentiment analysis) and visualization. Data collection uses Twitter Search API with 1000 Penari Desa keywords in Indonesian. The lexicon assessment results from 1000 tweets data obtained 33 positive, 767 neutral and 200 negative. The percentage of tweets containing positive comments by 3.3%, neutral 76.7% and negative by 20%